Test design and individual analysis in wheelchair rugby - Haydon, D. S.; Pinder, R. A.; Grimshaw, P. N.; Robertson, W. S. P. (Journal of Science and Medicine in Sport, 2018)
Objectives: Use a task vehicle of sprint testing in wheelchair rugby (WCR) to explore the impact of small changes to test design using both group and individual analysis.Design: Exploratory, repeated measures, on-court study Method: 25 national or international level wheelchair rugby players completed 5x 5m sprints under two conditions: (i) an acceleration from standstill in their own time, and (ii) an `active` start, simulating a key aspect of performance. Video analysis and accelerometer data were used to measure key kinematic and performance variables with a focus on the first three strokes. Each player was grouped into a high-, mid-, or low-point group based on their sport-specific classification score. Group (paired sample ttests) and individual (meaningful differences, performance coefficients, and Cohen`s d effect sizes) analysis assessed differences between the two conditions. Results: The low-point classification group performed significantly slower in the active start (p< 0.05). There were no differences in sprint time for the high- and mid-point groups. Mid-point players achieved greater peak accelerations for strokes two and three in the active start (p< 0.05). Individual sprint performances varied substantially, ranging from 8% decrease to 14% increase in sprint time for the active start. Meaningful differences in peak accelerations were demonstrated for 23 out of the 25 players.Conclusions: Small amendments to test design can lead to significant differences in individual athlete performance. Traditional group analyses masked important individual responses to testing conditions. There is need to further consider representative test design, and individual analysis for monitoring physical and skill performance.